2010
DOI: 10.3858/emm.2010.42.4.028
|View full text |Cite
|
Sign up to set email alerts
|

PKC-δ inhibitors sustain self-renewal of mouse embryonic stem cells under hypoxiain vitro

Abstract: Under hypoxia, mouse embryonic stem cells (mESCs) lose their self-renewal activity and display an early differentiated morphology mediated by the hypoxia-inducible factor-1α (HIF-1α). Previous studies have demonstrated that PKC-δ is activated by hypoxia and increases the protein stability and transcriptional activity of HIF-1α in human cancer cells. Furthermore, activation of PKC-δ mediates cardiac differentiation of ESCs and hematopoietic stem cells. However, the role of PKC-δ in hypoxia-induced early differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…S7B). We chose PKCδ because of a recent report 27 that implicated PKCδ inhibition in maintaining mESCs self-renewal in vitro . Compared to the PKCζkd cells, the expression of pluripotency genes, Oct4, Nanog and Sox2, were significantly induced when both PKCζ and PKCδ were knocked-down (Figure S7C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7B). We chose PKCδ because of a recent report 27 that implicated PKCδ inhibition in maintaining mESCs self-renewal in vitro . Compared to the PKCζkd cells, the expression of pluripotency genes, Oct4, Nanog and Sox2, were significantly induced when both PKCζ and PKCδ were knocked-down (Figure S7C).…”
Section: Resultsmentioning
confidence: 99%
“…In investigating the role of PKC during endothelial differentiation, however, we serendipitously found that inhibition of PKC signaling is sufficient to maintain, derive, and propagate pluripotent ES cells and also facilitates reprogramming of differentiated cells to induce pluripotency. Prior to this study, PKC isoforms have been studied during ES cell differentiation in different perspectives 1216 . However, the involvement of the PKC signaling pathway in ES cell pluripotency is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…erythropoiesis, cell proliferation and angiogenesis [2][3][4]. HIF expression is profound in primary tumor tissues and correlates with a poor prognosis in patients with various cancers [5][6][7][8].…”
mentioning
confidence: 99%
“…Rex1 and Fgf4 are representative markers for mESC stemness and self-renewal activity, whereas Fgf5 and Stat5a are markers for early differentiation (Lee et al , 2010). Expression levels of Rex1 and Fgf4 decreased under hypoxia; treatment with VPA blocked the suppression of the Rex1 and Fgf4 in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, we reported that PKC-δ inhibitors block the early differentiation of mESCs under hypoxia via the destabilization of HIF-1α (Lee et al , 2010). HDACIs effectively inhibited HIF-1α stability in cancer cells; however, the relevance of the HDACIs as regulators of self-renewal activity in hypoxia-induced differentiation in mESCs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%